Clinical performance of a diode laser fluorescence device for the detection of occlusal caries in primary teeth - KATERINA KAVVADIA, & PANAGIOTIS LAGOUVARDOS (IAPD and Blackwell, 2008)
Detection of early noncavitated occlusal caries presents many diagnostic problems in clinical practice when simple conventional diagnostic methods are used.